ANALYSIS OF PATIENT SATISFACTION WITH IMPORTANCE PERFORMANCE ANALYSIS AND CUSTOMER SATISFACTION INDEX (CASE STUDY: CITRA SUNDARI HOSPITAL) - Pratama, Oktioza; Muhammad Azhar Firdaus; Apfiasari, Steela; Maryani, Edna; Kurniati, Ary (UJoST- Universal Journal of Science and Technology, 2024)
Citra Sundari Hospital as the organizer of health efforts has the responsibility to provide health services to the entire community. Therefore, improving the quality of service is needed in an effort to attract patients to seek treatment at Citra Sundari Hospital. This research was conducted to determine the level of consumer satisfaction with hospital services and to find out what attributes are the main priority in improving service quality to improve service quality at Citra Sundari Hospital, by distributing closed questionnaires and calculating using the Importance Performance Analysis (IPA) method. and the Customer Satisfaction Index (CSI) method. From the calculation results of the Importance and Performance Analysis (IPA) method, the suitability level value is 100.43% and in the Cartesian diagram of 30 attributes there are 14 attributes that express service satisfaction at Citra Sundari Hospital, namely attribute numbers 1,3,4,6,7 , 10, 11, 12, 13, 18, 19 and 20. The results of the calculation of the Customer Satisfaction Index (CSI) method for Citra Sundari Hospital obtained a score of 92.17%, showing that Citra Sundari Hospital customers felt "Very Satisfied", so it could be said that the performance of Citra Sundari Hospital is very good and meets patient satisfaction with hospital services.